A low‐cost mesocosm for the study of behaviour and reproductive potential in Afrotropical mosquito (Diptera: Culicidae) vectors of malaria. Issue 1 (8th October 2014) - JACKSON, B. T.; STONE, C. M.; EBRAHIMI, B.; BRIËT, O. J. T.; FOSTER, W. A.
Abstract A large‐scale mesocosm was constructed and tested for its effectiveness for use in experiments on behaviour, reproduction and adult survivorship in the Afrotropical malaria vector Anopheles gambiae s.s. Giles (Diptera: Culicidae) in temperate climates. The large space (82.69 m3) allowed for semi‐natural experiments that increased demand on a mosquito's energetic reserves in an environment of widely distributed resources. A one‐piece prefabricated enclosure, made with white netting and vinyl, prevented the ingress of predators and the egress of mosquitoes. Daylight and white materials prompted the mosquitoes to seclude themselves in restricted daytime resting sites and allowed the easy collection of dead bodies so that daily mortality could be assessed accurately using a method that accounts for the loss of a proportion of bodies. Here, daily, age‐dependent mortality rates of males and females were estimated using Bayesian Markov chain Monte Carlo simulation. In overnight experiments, mosquitoes successfully located plants and took sugar meals. A 3‐week survival trial with a single cohort demonstrated successful mating, blood feeding, oviposition and long life. The relatively low cost of the mesocosm and the performance of the mosquitoes in it make it a viable option for any behavioural or ecological study of tropical mosquitoes in which space and seasonal cold are constraining factors.